Space and a Damaged Place: Philippine Migrant Transnational Engagement Following the Guinsaugon Landslide Disaster. Issue 6 (5th June 2015) - Loebach, Peter
Abstract: This study utilises a range of qualitative data sources to investigate migrant transnational activity occurring in response to a landslide disaster event that affected the Philippine village of Guinsaugon in February 2006. The disaster provoked multiple responses from village emigrants. A first wave of migrants returned to assist kin members directly affected by the disaster. A second wave of migrants arrived between 1 week and 3 months following the disaster to assist the community as a whole. One aiding organisation was formed by returned migrants who organised in their home community following the disaster. The ATHena Project: Advocacy for Transparency and Honesty was a civil society organisation that promoted accountability in the donation distribution process and also initiated political change. These activities were made possible by recent advances in information and` communication technologies and by the specific form of the weak Philippine state that enables the Philippine diaspora to emerge as a powerful social group. Copyright © 2015 John Wiley & Sons, Ltd.